Perancangan Buku Ilustrasi â€œJust Do (Odle) It!â€ - Effendi, Ade Kartika; Viatra, Aji Windu; Mubarat, Husni (Besaung : Jurnal Seni Desain dan Budaya)
Doodle is an activity that anyone can do it. This scribbling/doodling activity is often referred to as doodle. Lots of people who knowingly or unknowingly ever made a doodle. Doodle can be a beautiful work of art and bring the benefits to those who diligently it. But there is a problem for the doodle maker, itâ€™s the artwork that usually does not have character. That's because lack of information and knowledge about Doodle. Books about doodles are widely circulating in the market, but the problem is the Information & Knowlegde of Doodle Books stiil not available yet. Therefore an Illustration Book Design â€œJust Do(odle) it!â€ was created which aims to introduce and provide information and knowledge about doodle for the wider society.